METHODOLOGY FOR CAPACITY CALCULATION IN RAILWAY STATIONS USED IN IS KANGO (Perner's Contacts, 2013)
This paper deals with design of methodology for railway station capacity assessment that is in an experimental stage within the information system KANGO. This methodology is slightly different from procedure that is defined in obsolete regulation D24. These days the new methodology is in test stage. The reason for changes in methodology consist of finished reworks in module that is responsible for technological times – this module is basis for occupancy time calculation for running tracks and gridiron.
Keywords: capacity calculation; railway station; gridiron; running track; occupation period; change-over between station track and line track